53Mn‐53Cr dating of aqueously formed carbonates in the CM2 lithology of the Sutter's Mill carbonaceous chondrite. (7th August 2014) - Jilly, Christine E.; Huss, Gary R.; Krot, Alexander N.; Nagashima, Kazuhide; Yin, Qing‐Zhu; Sugiura, Naoji
Abstract Radiometric dating of secondary minerals can be used to constrain the timing of aqueous alteration on meteoritic parent bodies. Dolomite is a well‐documented secondary mineral in CM chondrites, and is thought to have formed by precipitation from an aqueous fluid on the CM parent body within several million years of accretion. The petrographic context of crosscutting dolomite veins indicates that aqueous alteration occurred in situ, rather than in the nebular setting. Here, we present 53Mn‐53Cr systematics for dolomite grains in Sutter's Mill section SM51‐1. The Mn‐Cr isotope data show well‐resolved excesses of 53Cr correlated with 55Mn/52Cr ratio, which we interpret as evidence for the in situ decay of radioactive 53Mn. After correcting for the relative sensitivities of Mn and Cr using a synthetic Mn‐ and Cr‐bearing calcite standard, the data yield an isochron with slope corresponding to an initial 53Mn/55Mn ratio of 3.42 ± 0.86 × 10−6. The reported error includes systematic uncertainty from the relative sensitivity factor. When calculated relative to the U‐corrected Pb‐Pb absolute age of the D'Orbigny angrite, Sutter's Mill dolomites give a formation age between 4564.8 and 4562.2 Ma (2.4–5.0 Myr after the birth of the solar system). This age is contemporaneous with previously reported ages for secondary carbonates in CM and CI chondrites. Consistent carbonate precipitation ages between the carbonaceous chondrite groups suggest that aqueous alteration was a common process during the early stages of parent body formation, probably occurring via heating from internal 26Al decay. The high‐precision isochron for Sutter's Mill dolomite indicates that late‐stage processing did not reach temperatures that were high enough to further disturb the Mn‐Cr isochron.